2016
DOI: 10.1111/neup.12347
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis identifies BRAF hotspot mutations associated with gliomas with peculiar epithelial morphology

Abstract: Brain tumors harbor various BRAF alterations, the vast majority of which are the BRAF kinase-activating V600E mutation. BRAF mutations are most frequently detected in certain subtypes of low-grade glioma, such as pilocytic astrocytoma (PA), pleomorphic xanthoastrocytoma (PXA), ganglioglioma (GG) and dysembryoplastic neuroepithelial tumor (DNT). However, it is unclear whether gliomas harboring BRAF mutations can be invariably regarded as these glioma subtypes or their derivatives. To address this question, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…Whereas most GGs histologically correspond to WHO grade I, GGs with anaplastic features are categorized as WHO grade III. 6 The histopathological diagnosis of our patient was GG; however, genetic analyses revealed that the tumor lacked the BRAF V600E mutation but carried the H3F3A K27M mutation. 4 Accordingly, this mutation can be used as a molecular marker and as a potential therapeutic marker for these phenotypes of gliomas.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Whereas most GGs histologically correspond to WHO grade I, GGs with anaplastic features are categorized as WHO grade III. 6 The histopathological diagnosis of our patient was GG; however, genetic analyses revealed that the tumor lacked the BRAF V600E mutation but carried the H3F3A K27M mutation. 4 Accordingly, this mutation can be used as a molecular marker and as a potential therapeutic marker for these phenotypes of gliomas.…”
Section: Discussionmentioning
confidence: 68%
“…6,7 Although IDH1/2 and BRAF V600E mutations were not detected, the H3F3A K27M mutation was clearly evident (Fig. Polymerase chain reaction, Sanger sequencing and high-resolution melting analyses of mutation hotspots on IDH1, IDH2, BRAF and H3F3A were performed as described in our previous study.…”
Section: Genetic Findingsmentioning
confidence: 97%
“…To verify the specificity in genetic backgrounds of IDH ‐mut pGBMs, we analyzed expression of glioma‐related genes. Our previous studies indicated that expression patterns of mesenchymal and proneural marker genes in GBMs can be measured by our original scoring scale, the P‐M score, which is defined by expression levels of six signature genes . As a result, the P‐M score of IDH ‐mutant ( IDH ‐mut) pGBM was significantly higher than that of IDH ‐wildtype ( IDH ‐wt) pGBM (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Sampling and DNA preparation were performed as previously described . PCR and sequencing of IDH1, IDH2 and TERT promoter were performed as previously described . The allelic status of chromosomes 1p, 10, 17p and 19q was evaluated by a PCR‐based LOH assay as previously described …”
Section: Methodsmentioning
confidence: 99%
“…2,3 Although IDH1/2 and BRAF V600E mutations were not detected, the H3F3A K27M mutation was clearly evident (Fig. Polymerase chain reactions (PCR), Sanger sequencing, and high-resolution melting analyses of mutation hotspots on IDH1, IDH2, TERT, BRAF, and H3F3A were performed as described in our previous study.…”
Section: Genetic Findingsmentioning
confidence: 99%